2022
DOI: 10.3390/nu14102156
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose Suppresses Lysosomal Anomalies in Supporting Cells of Oocytes and Maintains Female Fertility

Abstract: Supporting cells of oocytes, i.e., cumulus cells, control oocyte quality, which determines fertilization success. Therefore, the transformation of mature and immature cumulus cells (MCCs and ICCs, respectively) into dysmature cumulus cells (DCCs) with dead characteristics deteriorates oocyte quality. However, the molecular basis for this transformation remains unclear. Here, we explored the link between autophagic decline and cumulus transformation using cumulus cells from patients with infertility, female mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…These results indicated that these key regulatory molecules could help yak cumulus cells maintain autophagy and endocytic activity during development. Recently, some studies have pointed out that the addition of melatonin, trehalose and other substances in vitro contributes to oocyte development (33,34), while EGF, as an important paracrine factor in follicles and a commonly used nutritional supplement in vitro culture, plays a crucial role in regulating cumulus cell growth, oocyte maturation and early embryonic development (19,21,23). To further investigate the function of EGF in the regulation of autophagy and endocytosis of cumulus cells, we detected the expression of related genes and proteins in cumulus cells treated with different concentrations of EGF and gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that these key regulatory molecules could help yak cumulus cells maintain autophagy and endocytic activity during development. Recently, some studies have pointed out that the addition of melatonin, trehalose and other substances in vitro contributes to oocyte development (33,34), while EGF, as an important paracrine factor in follicles and a commonly used nutritional supplement in vitro culture, plays a crucial role in regulating cumulus cell growth, oocyte maturation and early embryonic development (19,21,23). To further investigate the function of EGF in the regulation of autophagy and endocytosis of cumulus cells, we detected the expression of related genes and proteins in cumulus cells treated with different concentrations of EGF and gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a rational success rate of pharmacotherapies (GnRH agonists OCP, selective serotonin reuptake inhibitors benzodiazepines) and non-pharmacological management (aerobic exercise, cognitive behavioural therapy, reduction in caffeine intake, education, and increased calcium and carbohydrate intake) for PMS, these therapies have considerable side effects [5,7,8]. Women may also prefer and are inclined towards complementary and alternative treatment/therapies (CAMS), including nutritional supplements and herbal medicines over medical or surgical treatment [9][10][11]. Various Unani medicinal plants [12] have been expected to lessen PMS symptoms, as they are beneficial natural substitutes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Two articles focused on carbohydrates [13,14]. Salcedo and colleagues wrote an opinion article that encourages a lifestyle-based intervention such as therapeutic carbohydrate restriction as prevention and potential treatment of all gynecologic disorders that lead to Abnormal Uterine Bleeding [13].…”
mentioning
confidence: 99%
“…On the other hand, the disaccharide trehalose is a naturally occurring carbohydrate that may be useful to promote good health because of its properties that do not stimulate rapid increases in blood glucose. The experimental study of Kang et al showed that trehalose suppresses lysosomal anomalies in supporting cells of oocytes, suggesting a possible therapeutic effect on female fertility, although the clinical use remains speculative and limited [14].…”
mentioning
confidence: 99%